STANDAR PEMBERIAN NAFKAH KEPADA ISTRI PERSPEKTIF FILSAFAT HUKUM ISLAM - Mu’in, Fathul; Santoso, Rudi; Mas’ari, Ahmad (ASAS, 2020)
Life and the harmony of Muslim households cannot be separated from the name of the income. A mandatory income because of the legitimate contract, the surrender of the wife to the husband. The living is only required for a husband because of the demands of the marriage contract and because of the sustainability of fun as the wife must obey her husband, always accompanying it, regulating the household, educating her children. Having is the main responsibility of a husband and his wife's main right. If given to the wife with a chest, without the slightest element of the master, it is the main contribution that can bring the balance and happiness of households. However, in practice, not a few husbands who did not provide a living wife and child. There are also some husbands even if their husbands provide a living in accordance with household welfare standards. Based on the phenomenon it is necessary to research and analyze the standard of living husband to wife in the perspective of the philosophy of Islamic law law. This research concludes the legal income is mandatory. The fulfillment of the living that becomes shopping is in the form of basic needs, such as eating, residence, education and others. Regarding the levels or size of the income that must be met by parents to children or husbands there is nothing certain, because it must be seen from the ability of the livelihood. In terms of philosophical, husband's obligations provide for a wife having great wisdom. When becoming a wife, the wife is shackled with marriage and has an obligation to obey her husband. Therefore the need for a wife is the responsibility of the husband.Keywords: Brivans, Philosophy, Islamic Law